INTEGRATING ISLAMIC ECONOMICS AND ENVIRONMENTAL SUSTAINABILITY: A SYSTEMATIC LITERATURE REVIEW INTEGRASI EKONOMI SYARIAH DAN KEBERLANJUTAN LINGKUNGAN: TINJAUAN LITERATUR SISTEMATIS (SLR) - Dede Aji Mardani; Imas Siti Masuroh (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to systematically analyze the integration between Islamic economics and environmental sustainability using a Systematic Literature Review (SLR) approach. Data were collected from the Scopus database using keywords related to Islamic economics, Islamic finance, and sustainable development. A total of 22 selected articles were analyzed using a thematic approach to identify methodological patterns, research trends, and key findings. The results indicate that Islamic economics has a strong normative foundation in supporting sustainability through principles of justice, balance, and social welfare. However, a significant gap remains between theoretical concepts and empirical implementation, particularly in integrating environmental dimensions. In addition, Islamic social finance instruments such as zakat and waqf have not been optimally utilized in environmental sustainability contexts. The study also reveals methodological fragmentation and the absence of integrative models combining Islamic economics with green economy and circular economy approaches. Therefore, this study proposes an integrative framework that combines Islamic economic principles, sustainability paradigms, and Multi-Criteria Decision Analysis (MCDA) as both a theoretical and practical contribution. This research is expected to provide a new direction for the development of Islamic economics as an alternative model for achieving sustainable development.